New Iterative Method for Fractional Gas Dynamics and Coupled Burger’s Equations - Mohamed S. Al-luhaibi (The Scientific World Journal)
This paper presents the approximate analytical solutions to solve the nonlinear gas dynamics and coupled Burger’s equations with fractional time derivative. By using initial values, the explicit solutions of the equations are solved by using a reliable algorithm. Numerical results show that the new iterative method is easy to implement and accurate when applied to time-fractional partial differential equations.